1998
DOI: 10.1111/j.1399-6576.1998.tb05103.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arterial carbon dioxide tension on systemic vascular resistance in patients undergoing cardiopulmonary bypass

Abstract: This study demonstrates that during hypothermic cardiopulmonary bypass, systemic vascular resistance under alpha-stat acid-base management is higher than under pH-stat management. As obvious from measurements during the control period, this finding can be completely explained by the difference in PaCO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…The findings of our study are quite contrary to that of Buhre and colleagues (23) who concluded that SVR under c~ star' acid base management is higher than under 'pH stat' management. The drawback of the study done by Buhre and colleagues (23) was that it was performed in a randomized cross over design and each patient served as his own control.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of our study are quite contrary to that of Buhre and colleagues (23) who concluded that SVR under c~ star' acid base management is higher than under 'pH stat' management. The drawback of the study done by Buhre and colleagues (23) was that it was performed in a randomized cross over design and each patient served as his own control.…”
Section: Discussioncontrasting
confidence: 99%
“…The drawback of the study done by Buhre and colleagues (23) was that it was performed in a randomized cross over design and each patient served as his own control. Secondly the target values for cr stat' and 'pH stat' management were not reached.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in capillary hydrostatic pressure is likely to be caused by intensive peripheral sympathetic vasoconstriction 22,29 and venous dilatation from CO2 retention. 30 The observed cell counts in the present study were corrected for plasma volume changes and, therefore, the increases in RBCV and WBC were not due to haemoconcentration (on the contrary, haemodilution was observed) but were, rather, caused, at least in part, by splenic contraction. 7,31 In the present study, an increase in RBCV in response to serial breath holds in professional divers and intact subjects without diving experience was found.…”
Section: Discussionmentioning
confidence: 94%
“…1 Cerebral autoregulation is a complex physiologic mechanism, which is influenced by several factors including hematocrit and p a CO 2 . 21,22 Ono et al studied cerebral autoregulation during CPB and found increased p a CO 2 levels to be a factor of negative influence. 15 As indicated by the authors' data, dCA was reduced with a lower hematocrit ( Table 3).…”
Section: Discussionmentioning
confidence: 98%